Yes, It's that Common and Yes, It's that Bad: An Estimation of the Prevalence and Psychological Correlates of Rape and Sexual Assault in College Women - Trierweiler, Emma J; Pashak, Travis J; Bradley, Sophia M (Psychological reports, 2024)
Rape myths play a role in rape denialism, in which individuals deny the prevalence and severity of sexual assault. This project aimed to address two common rape myths: that rape is uncommon and its effects are exaggerated. To test these claims, we explored two archival samples consisting of undergraduate women. Study 1, a 5-year chart review of university counseling center intake forms ( = 883), demonstrated that 30.2% of clients had experienced "sexual violence," "sexual contact without consent," or both. Study 2, a re-analysis of an emerging adulthood resilience survey dataset ( = 359), demonstrated that 20.6% of subjects had a history of sexual assault, and that those women reported lower life satisfaction and more severe psychological symptoms than those who did not. These findings are in line with previous literature debunking harmful rape myths that contribute to the perpetuation of rape culture. Our data help validate these rape notions as mythical; rape is indeed common and devastating.